Analisis Penyelesaian Sengketa Kepemilikan Tanah di Desa Patemon Kecamatan Tlogosari Kabupaten Bondowoso - Farhan Agil; Heriyanto Heriyanto; Fathorrahman Fathorrahman (Referendum : Jurnal Hukum Perdata dan Pidana, 2024)
Land ownership disputes are a common issue in Indonesia, particularly considering that land is a highly valuable asset for the community. Conflicts related to land ownership not only impact individuals but can also trigger disputes involving communities and families. The Certificate of Ownership Rights (SHM) serves as legal proof of land ownership and plays a crucial role in resolving disputes. This study aims to analyze the evidentiary strength of SHM in resolving land disputes in Bondowoso Regency. By using normative legal research methods, this study explores the role of SHM within the context of Indonesia's positive law and how this certificate is applied in dispute cases. The findings indicate that SHM possesses strong evidentiary power in resolving land disputes, provided its validity is recognized and supported by effective law enforcement.